The Changing Role of a Librarian in Knowledge Management Environment (Paper B) - Nikam, Khaiser (Journal of Information and Knowledge, 2013)
We are living in the Information Knowledge Era (IKE), which is fast changing. In this rapidly changing IKE, knowledge and information are the most vital resources, for the growth and development of both individuals and organizations. These resources are assets, which are available in the form of databases, knowledge bases and in the minds of people and organizations. Very often one part of the organization repeats the work of another part, simply because, they are not aware of what is going on in the other parts of the organization. Hence it is important to know what the knowledge management assets are? And how to manage and make the best use of these assets to reap maximum returns. In the age of IKE librarians’ role is also changing and they are posed with many challenges. Some times we wonder as to what the role of a librarian is in a KM library. This article finds answers from some of the common doubts that arise in our mind .The paper also presents the shift from the conventional role to the fast changing KM roles of a librarian .It also emphasizes on how information management is the domain of librarians and KM is only an extension, where IT is the enabler.